Assessment of the potential for developing a micro-launcher industry in South Africa - Campbell, Victoria (Department of Electrical Engineering, 2020)
Small satellites have dramatically lowered the barriers to participating in space activities for many emerging countries, including South Africa. The rapid up-take of this facet of space technology has spurred the development of several micro-launchers dedicated to lofting small satellites to low Earth orbit. However, the majority of these micro-launcher initiatives and the majority of spaceports in use are located in the northern hemisphere, and there are currently no operational spaceports in Africa. In this study the potential for developing a micro-launcher industry in South Africa is explored, building on the launch facilities established for the previous space programme of the 1980s and early 1990s, and existing capabilities in present-day academic institutions and industry. Potential markets, financial requirements, technical feasibility, available infrastructure, and regulatory and policy aspects of such a venture are reviewed with respect to South Africa’s current political situation and attitude towards space activities. Several possible options for establishing small satellite launch capabilities in South Africa are used as a framework to assess the feasibility of a micro-launcher industry in South Africa. These range from a simple “ship and shoot” scenario with no indigenously developed technology to more complex cooperative arrangements which would, to varying degrees, require technology transfers and cooperation with potential international partners.